Perubahan perilaku kader dalam upaya peningkatan pengetahuan dan sikap wanita usia Subur (WUS) tentang ASI-eksklusif di desa Talang Mulya Lampung - Wahid Tri Wahyudi; Nita Evrianasari (Holistik Jurnal Kesehatan, 2020)
Knowledge and attitude towards exclusive breastfeeding among women of childbearing age and empowerment by health worker cadresBackground:  Health worker cadres  are one of the frontline maternal and child health service providers, they are have an important role in empowering the community and providing convenience to the community in obtaining basic health services because they are the ones who best understand the conditions of the community's needs in the region. At Talang Mulya Village, they are have not had a significant influence on changes in public health behavior, especially in exclusive breastfeeding extension services they need more a adequate knowledge and skills.Purpose: Knowing changing in knowledge and attitude towards exclusive breastfeeding among women of childbearing age and empowerment by health worker cadresMethod: Quantitative research with the research design "Quasy Experimental Pre-Post Test” and using T-Test Paired. The population was the  health worker cadres and women of childbearing age  at Talang Mulya-Pesawaran. The sampling technique for  women of childbearing age used random sampling taken of 30 respondents, and health worker cadres as total sampling of 8 respondents.Results: There was changing in knowledge and attitude towards of health worker cadres (p. Value = 0,000) and increasing in  knowledge and attitude towards exclusive breastfeeding among women of childbearing age (p.value = 0,000) and attitude (p.value = 0,001) about exclusive breastfeeding after empowering by health worker cadres.Conclusion: Empowerment of village health worker cadres has an influence on increasing in knowledge among women of childbearing age  and attitude about exclusive breastfeeding.Keywords: Knowledge; Attitudes; Exclusive breastfeeding; Women of childbearing age; Empowerment; Health worker cadresPendahuluan: Kader Posyandu merupakan salah satu tenaga penyelenggara pelayanan kesehatan ibu dan anak di lini terdepan yang memiliki peranan penting dalam memberdayakan masyarakat dan memberikan kemudahan kepada masyarakat dalam memperoleh pelayanan kesehatan dasar dikarenakan merekalah yang paling memahami kondisi kebutuhan masyarakat di wilayah tersebut. Pada kenyataannya kader posyandu khususnya di Desa Talang Mulya belum memberikan pengaruh yang signifikan terhadap perubahan perilaku Kesehatan masyarakat khususnya pada pelayanan penyuluhan ASI eksklusif dikarenakan banyaknya kader yang belum memiliki pengatahuan dan keterampilan yang memadai dalam menjalankan tugasnya.Tujuan: Diketahui peningkatan pengetahuan dan sikap WUS tentang ASI eksklusif melalui peningkatan pemberdayaan kader.Metode: Penelitian kuantitatif dengan desain penelitian “Quasy Experimental Pre-Post Test” dan menggunakan T-Test Paired. Populasi penelitian adalah kader serta WUS di Desa Talang Mulya-Pesawaran. Tekhnik pengambilan sampling untuk wanita usia subur menggunakan quota sampling dengan quota 30 responden yang diambil secara ramdom sedangkan pengambilan sampling kader menggunakan total sampling yaitu berjumlah 8 orang. Instrumen penelitian menggunakan kuisioner.Hasil: Terdapat perubahan perilaku kader (P.Value=0,000) serta peningkatan pengetahuan (P.Value=0,000) dan sikap (P.Value=0,001) WUS tentang ASI-Eksklusif setelah dilakukan pemberdayaan terhadap kader.Simpulan: Pemberdayaan terhadap kader memberikan pengaruh terhadap peningkatan pengetahuan dan sikap WUS.